"Why can't you pay if you can eat?": Tales of How Women Encounter Unpleasant NGO Practices in Bangladesh. Issue 2 (1st June 2020) - Ali, H M Ashraf
Abstract: In Bangladesh and globally, microcredit has been recognized as a key development tool in the alleviation of poverty. Many international development agencies and donor countries prioritize microcredit to alleviate poverty because of reported success stories of microcredit nongovernmental organizations (NGOs) in mobilizing poor women to participate in incomegenerating activities. Microcredit NGOs construct success stories of alleviating poverty and gender equity in relation to the repayment rate, but little is known about how they deploy strategies to collect loan installments from borrowers. Using ethnographic data collected in the Chittagong Hill Tracts (CHT) of Bangladesh, I examine how microcredit NGOs create unequal power relations between fieldworkers and borrowers to facilitate secure loan recovery. Reflecting on the women's experiences with microcredit programs, I demonstrate how these microcredit NGOs impose the provision of group liabilities, a 'forced choice, ' upon the borrowers and how they socialize the borrowers into a culture of shaming to enforce repayment obligations. Instead of contributing to the development of norms of cooperation and solidarity that socially and economically empower the entire community, I argue that NGOs instead empower a group of female borrowers, serving their capitalistic interests, which often stimulates social conflict and negatively affects social solidarity.